The Inventory of Personality Organisation: its psychometric properties among student and clinical populations in Japan - Hasui Chieko; Shono Masahiro; Mitoma Hiroshi; Kikuchi Hiroyoshi; Kano Rikihachiro; Igarashi Hiromi; Kitamura Toshinori (Annals of General Psychiatry, 2009)
Abstract Background The Inventory of Personality Organisation (IPO) is a self-report measure that reflects personality traits, as theorised by Kernberg. Methods In study 1, the Japanese version of the IPO was distributed to a population of Japanese university students (N = 701). The students were randomly divided into two groups. The factor structure derived from an exploratory factor analysis among one subsample was tested using a confirmatory factor structure among another subsample. In study 2, the factor-driven subscales of the IPO were correlated with other variables that would function as external criteria to validate the scale in a combined population of the students used in study 1 and psychiatric outpatients (N = 177). Results In study 1 the five-factor structure presented by the original authors was replicated in exploratory factor analyses in one subgroup of students. However, this was through reduction of the number of items (the number of the primary items was reduced from 57 to 24 whereas the number of the additional items was reduced from 26 to 13) due to low endorsement frequencies as well as low factor loadings on a designated factor. The new factor structure was endorsed by a confirmatory factor analysis in the other student subgroup. In study 2 the new five subscales of the Japanese IPO were likely to be correlated with younger age, more personality psychopathology (borderline and narcissistic), more dysphoric mood, less psychological well-being, more insecure adult attachment style, lower self-efficacy, and more frequent history of childhood adversity. The IPO scores were found to predict the increase in suicidal ideation in a week's time in a longitudinal follow-up. Conclusion Although losing more than 40% of the original items, the Japanese IPO may be a reliable and valid measure of Kernberg's personality organisation for Japanese populations.